The Impact of Work-Family Conflict and Job Satisfaction on Turnover Intention at PT Suzuki Indomobil Motor Cikarang - Muhtar Gojali; Anita Novialumi (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
The purpose of this study was to determine how job satisfaction and work-family conflict (WFC) affect employee satisfaction and their intention to leave PT Suzuki Indomobil Motor Cikarang. Conflict between the demands of family life and work can affect job satisfaction and intention to leave. Data collected from 94 employees were analyzed using quantitative multiple linear regression techniques. The results showed that WFC significantly influenced intention to leave, while job satisfaction significantly influenced intention to leave. If an employee faces significant work-family conflict, they are likely to have low levels of job satisfaction and may leave the company. These results demonstrate the importance of managing work-family conflict and striving to increase job satisfaction to lower turnover. Based on the results of this study, this research helps human resource management in creating policies that reduce turnover and create a more balanced work environment.